2018
DOI: 10.2337/dc18-1581
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Management Indicator (GMI): A New Term for Estimating A1C From Continuous Glucose Monitoring

Abstract: While A1C is well established as an important risk marker for diabetes complications, with the increasing use of continuous glucose monitoring (CGM) to help facilitate safe and effective diabetes management, it is important to understand how CGM metrics, such as mean glucose, and A1C correlate. Estimated A1C (eA1C) is a measure converting the mean glucose from CGM or self-monitored blood glucose readings, using a formula derived from glucose readings from a population of individuals, into an estimate of a simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
361
6
16

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(424 citation statements)
references
References 16 publications
9
361
6
16
Order By: Relevance
“…The patterns were generally similar with definition of average glucose as OGTT fasting glucose alone [as used by Hempe et al [3] in their analysis of data from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial], and as the mean of OGTT fasting glucose and OGTT 2-h glucose (Table S2). With all three definitions of average glucose, the regressions for the OGTT diabetes group in the present study [early in their natural history, with mean HbA 1c of 44 mmol/mol (6.2%) and diabetes which was previously unrecognized] had a slope that was less steep than the slope of the regression found in the A 1c -Derived Average Glucose (ADAG) study [4] and the slopes observed in patients with diabetes who were later in their natural history and who had higher mean HbA 1c [10,11]. Within each normal, prediabetes and diabetes OGTT group, participants were divided into mismatch tertiles of HGI, as low, intermediate and high, then each tertile was combined across the OGTT groups (e.g.…”
Section: Cohort Characteristicscontrasting
confidence: 62%
See 1 more Smart Citation
“…The patterns were generally similar with definition of average glucose as OGTT fasting glucose alone [as used by Hempe et al [3] in their analysis of data from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial], and as the mean of OGTT fasting glucose and OGTT 2-h glucose (Table S2). With all three definitions of average glucose, the regressions for the OGTT diabetes group in the present study [early in their natural history, with mean HbA 1c of 44 mmol/mol (6.2%) and diabetes which was previously unrecognized] had a slope that was less steep than the slope of the regression found in the A 1c -Derived Average Glucose (ADAG) study [4] and the slopes observed in patients with diabetes who were later in their natural history and who had higher mean HbA 1c [10,11]. Within each normal, prediabetes and diabetes OGTT group, participants were divided into mismatch tertiles of HGI, as low, intermediate and high, then each tertile was combined across the OGTT groups (e.g.…”
Section: Cohort Characteristicscontrasting
confidence: 62%
“…Regressions of HbA 1c levels (mmol/mol) vs average glucose (AG) levels (mmol/L),for all participants and glycemic status groups, based on oral glucose tolerance test (OGTT) glucose levelsnormal glucose metabolism (normal), prediabetes, and diabetes, defined as in Methodsand with average glucose defined as OGTT fasting glucose alone, the mean of OGTT fasting glucose and OGTT 2-h glucose, and the mean of OGTT fasting glucose, OGTT 2-h glucose, and GCT 1-h glucose levels. Also included for comparison are regressions from the A 1c -Derived Average Glucose (ADAG) study (including both diabetes and nondiabetes, and average glucose based on CGM and SMBG) [5]) and those recently reported by Beck et al [11] and Bergenstal et al [12] [including only diabetes, and average glucose based on CGM]; the participants with diabetes in these three studies were later in their natural histories, with higher HbA 1c levels, compared to those with previously unrecognized diabetes in the present study. Table S3.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Historically, this has been represented by an average glucose, which in theory could be converted to an estimated HbA 1c . However, this is not exactly accurate and has led to a call to consider a new metric: glucose management indicator (GMI) [14]. The GMI is proposed as a new indicator for clinical reports such as the ambulatory glucose profile that rephrases the CGM data to a similar and correlated number for HbA 1c but avoids the troublesome lexicon of estimated HbA 1c , which should be used carefully and only in the context of formulas designed to produce estimates of real HbA 1c values, not derivatives of average blood glucose [15].…”
Section: Clinical Scenario 1: Utility Of Cgmmentioning
confidence: 99%
“…Using a standard formula, a value called “estimated HbA 1c ” was generated from the mean glucose, and the term was later replaced by “glucose management indicator” (GMI). Many patients and clinicians find the GMI to be a helpful educational tool in understanding the CGM‐generated glucose profiles and will facilitate optimal diabetes management and the adjustment of anti‐diabetic therapy …”
Section: Cgm Parametersmentioning
confidence: 99%